Genetic Polymorphisms and Clinical Features in Diabetic Patients With Fatty Liver: Results From a Single-Center Experience in Southern Italy - Villani, Rosanna; Magnati, Grazia Pia; De Girolamo, Giuseppe; Sangineto, Moris; Romano, Antonino Davide; Cassano, Tommaso; Serviddio, Gaetano (Frontiers in Medicine, 2021)
Genetic background may be involved in the promotion and progression of non-alcoholic fatty liver disease (NAFLD). Previous studies have suggested that the single nucleotide polymorphisms (SNPs) may be associated with the specific clinical features in the patients with hepatic steatosis; however, data on the patients with diabetes from Southern Italy are lacking. We enrolled 454 patients and 260 of them had type 2 diabetes. We studied the PNPLA3 rs738409, LPIN1 rs13412852, KLF6 rs3750861, SOD2 rs4880, TM6SF2 rs58542926, and ZNF624 rs12603226 SNPs and their distribution in the study population. Lipid profile, liver stiffness, and kidney function were also studied to understand the potential role of the SNPs in the development of clinical phenotypes. No differences were observed in the distribution of polymorphisms between the diabetic and non-diabetic subjects. Carriers of risk allele G for PNPLA3 rs738409 SNP showed a lower mean value of serum triglycerides and a higher liver stiffness. Risk allele for KLF6 rs3750861 and SOD2 rs4880 polymorphism had a lower estimated glomerular filtration rate (eGFR) value, whereas no differences in the glucose and glycated hemoglobin level were observed in the subgroups by the different genotypes. Genetic polymorphisms are useful to identify the patients at higher risk of development of liver fibrosis and lower eGFR values in the patients with diabetes and NAFLD. Their use in clinical practice may help the clinicians to identify the patients who require a more strict follow-up program.